A full time scale resilience improvement strategy of distribution network under extreme weather. (August 2022) - Ding, Yixin; Lu, Tianfeng; Wang, Zhiyu; Wu, Houyi; Lu, Xuewen
Abstract: To improve the resilience of power distribution systems to fight natural disasters caused by extreme weather, A framework for enhancing disaster resilience at the full time scale is proposed. First, the influence of extreme weather events on power system components is analyzed, the failure probability of system components during extreme weather is evaluated. Then the vulnerability model of the components is established and the multi-stage performance response curve is used to quantify the resilience level of the network in each period. On this basis, framework of disaster resilience enhancement at full time scale before, during and after the occurrence of disasters is proposed. In the pre-failure phase, preventive strategies can be used to avert serious losses. Planning model of distributed power supply and tie line in distribution network based on active resilience lifting strategy during disaster. This paper presents the problem of flexible distribution system planning with resource redistribution and minimizing the cost of post-failure operation and load reduction as objective functions. After a fault occurs, maintenance measures for the faulty components could be optimized to restore the resilience of the distribution network as effectively as possible. Finally, the proposed strategy was applied to an ice and snow disaster in northern China in 2008 to study the effectiveness of the strategy in practical application.